What we know about acquisition of adult literacy : is there hope? - Abadzi, Helen (Washington, D.C. : World Bank, 1994)
This publication discusses findings related to the acquisition of literacy in light of cognitive psychology principles and proposes applications that may make literacy projects more effective
Includes bibliographical references (p. [78]-89) and index.
osc 04/03/2019
Loans
Keywords: Functional literacy; Literacy programs